2010
DOI: 10.3174/ajnr.a2069
|View full text |Cite
|
Sign up to set email alerts
|

Combined Diffusion Imaging and MR Spectroscopy in the Diagnosis of Human Prion Diseases

Abstract: BACKGROUND AND PURPOSE:The physiopathologic bases underlying the signal intensity changes and reduced diffusibility observed in prion diseases (TSEs) are still poorly understood. We evaluated the interest of MRS combined with DWI both as a diagnostic tool and a way to understand the mechanism underlying signal intensity and ADC changes in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 36 publications
1
39
0
2
Order By: Relevance
“…Other reports have suggested that PrP Sc plaque deposition might be responsible for the decreased water diffusivity (11,20). One recent MR spectroscopy study used metabolites as surrogate markers of histological changes further supported a role of prion protein deposition in the production of diffusion restriction (11). Neuronal stress, which results in neuropil vacuolization, should theoretically decrease the N-acetyl-aspartate (NAA) levels whereas astrocytosis should increase myoinositol.…”
Section: Neuroimagingmentioning
confidence: 99%
See 4 more Smart Citations
“…Other reports have suggested that PrP Sc plaque deposition might be responsible for the decreased water diffusivity (11,20). One recent MR spectroscopy study used metabolites as surrogate markers of histological changes further supported a role of prion protein deposition in the production of diffusion restriction (11). Neuronal stress, which results in neuropil vacuolization, should theoretically decrease the N-acetyl-aspartate (NAA) levels whereas astrocytosis should increase myoinositol.…”
Section: Neuroimagingmentioning
confidence: 99%
“…MRI is far more sensitive, especially with the addition of FLAIR and diffusionweighted imaging (DWI). DWI is the most useful sequence with reported sensitivity ranging from 86 to 94% (8)(9)(10)(11). DWI also benefit from greater inter-observer agreement compared with FLAIR or T2 (8).…”
Section: Neuroimagingmentioning
confidence: 99%
See 3 more Smart Citations